2022
DOI: 10.1111/1759-7714.14775
|View full text |Cite
|
Sign up to set email alerts
|

Non‐small cell lung cancer with EGFR (L858R and E709X) and CNNB1 mutations responded to afatinib

Abstract: Lung cancer with complex epidermal growth factor receptor (EGFR) and CTNNB1 comutations is rare, and the efficacy of tyrosine kinase inhibitors (TKIs) is generally poor. Here, we encountered a lung cancer patient with complex EGFR (L858R and E709X) and CTNNB1 comutations who successfully responded to afatinib. A 78‐year‐old woman visited our hospital with a cough and bloody sputum that had worsened over the past year. She had multiple mass shadows in both lungs and nodular shadows in the bronchi. The patient w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The copyright holder for this this version posted March 13, 2024. ; https://doi.org/10.1101/2024.03.11.24304129 doi: medRxiv preprint reports or small series studies [67][68][69][70][71]. In vitro experiments using G719X mutant cell lines and patient-derived xenografts (PDX) demonstrated that osimertinib effectively inhibits signaling pathways and cellular growth, leading to sustained tumor growth inhibition [72].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The copyright holder for this this version posted March 13, 2024. ; https://doi.org/10.1101/2024.03.11.24304129 doi: medRxiv preprint reports or small series studies [67][68][69][70][71]. In vitro experiments using G719X mutant cell lines and patient-derived xenografts (PDX) demonstrated that osimertinib effectively inhibits signaling pathways and cellular growth, leading to sustained tumor growth inhibition [72].…”
Section: Discussionmentioning
confidence: 99%
“…Limited knowledge exists from G719X, mostly based on isolated case reports or small series studies [62][63][64][65][66]. In vitro experiments using G719X mutant cell lines and patient-derived xenografts (PDX) demonstrated that osimertinib effectively inhibits signaling pathways and cellular growth, leading to sustained tumor growth inhibition [67].…”
Section: Discussionmentioning
confidence: 99%